2013
DOI: 10.1155/2013/725452
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Analyze the Effectiveness of the Holes Healing Scheme in Wireless Sensor Network

Abstract: Because of the maturation of wireless technologies, the wireless sensor network has been used in various applications, especially in the environmental monitoring. After the nodes are deployed on the surveillance field, nodes will die due to the limited energy of the node or accidental events, inducing the coverage holes and the break of the transference path. To tackle this problem, researchers had proposed the rebuild network topology, such as adding Relay nodes. However, it costs a lot to build such a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…They used the principle of non-uniform node distribution to ensure energy balancing and extend the network lifetime Lin et al [62] They focused on the cost proposed a device provisioning framework in accordance with hierarchical communication architecture. Based on the application scenario, device provisioning strategies can be either random or deterministic.…”
Section: Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…They used the principle of non-uniform node distribution to ensure energy balancing and extend the network lifetime Lin et al [62] They focused on the cost proposed a device provisioning framework in accordance with hierarchical communication architecture. Based on the application scenario, device provisioning strategies can be either random or deterministic.…”
Section: Referencesmentioning
confidence: 99%
“…Mhatre and Rosenberg [62], authors described the proportionality between the number of regular sensors and the square of the number of CHs. By analyzing two modes of communication between the BS and the sensors, they concluded that for path loss = 2, multi-hop communication was useless.…”
Section: Optimal Number Of Coronasmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [9] surveyed the mobility approach for topology healing in wireless sensor networks. Two main mobility strategies can be listed: mobility of sensor nodes [10]- [12] and the deployment of additional mobile robots [13]. Ghosh et al show in [10] that Voronoi Diagrams can be used to detect and heal topology change problems like coverage or energy holes.…”
Section: Related Workmentioning
confidence: 99%
“…Active redundant nodes must derive hole information and calculate the healing efficiency before moving, a method which may induce erroneous movement and result in wasted energy. Besides the problem of energy consumption, the speed of the mobile nodes' movement is a critical issue which will affect the efficiency of the healing scheme; see [20] for further details. Authors in [21] considered a small group of mobile robots operating in WSNs and proposed the randomized robot-assisted relocation of static sensors (R3S2) and a grid-based variant (G-R3S2) algorithm for hole identification and coverage repair.…”
Section: Related Workmentioning
confidence: 99%